Distribution and release of human pancreatic polypeptide. Issue 12 (December 1976) - Adrian, T E; Bloom, S R; Bryant, M G; Polak, J M; Heitz, P H; Barnes, A J
Abstract : A simple and reliable radioimmunoassay has been developed for a new gut hormone, HPP. In the primate 93% of the total PP was found in the pancreas with a small amount throughout the remaining gastrointestinal tract. HPP has been shown to be produced by a number of pancreatic apudomas and their metastases. The immunoreactive PP from these tumours and from normal pancreas was chromatographically indistinguishable from the pure peptide. The plasma PP concentration rose rapidly after a meal in normal subjects and was still raised six hours later. Fasting plasma PP levels in patients with PP cell containing pancreatic endocrine tumours were higher than even the postprandial level in normal subjects. PP measurements is thus useful in diagnosis of pancreatic endocrine tumours.